Assessing the visual quality of the rainforest trail at Penang Botanical Garden / Noralizawati Mohamed, Dr. Noriah Othman and Associate Proffesor Dr. Mohd Hisham Ariffin - Mohamed, Noralizawati; Othman, Dr Noriah; Ariffin, Dr Mohd Hisham (Research Management Institute (RMI), 2011)
Gardens are positive elements of our urban environment and landscape. They are created to preserve existing vegetation and for enhancing the natural environment besides bring the benefits for human emotionally, intellectually, socially and physically. And today, the numbers of restoration and implementation for garden in urban area in Malaysia have increased in variety of types such as the botanical garden. As referred to National Landscape Department, a high number of Botanical Garden is being developed in Malaysia such as in Johor, Selangor, Perak and Terengganu. This future planning received a positive feedback by the public and experts. According to its achievements and contributions, therefore, the Penang Botanical Garden is officially taken as good example of successful Botanical Garden in Malaysia However, a forum on Penang Botanical Garden 2008 highlighted that the current development is being undertaken without any reference to the 1989 Botanical Development Master Plan thus the ignorance of this particular aspect would result to incoherent garden appearance. It is strongly believed that developing a Botanical Garden is not just improving the urban ecosystem and preserves the environment, it is also about visitor's satisfaction and perceptions towards the visual quality of the garden. Therefore, research on visual quality assessment in Penang Botanical Garden is very important to be made as part of restructuring process of the garden.